REMEDIASI MISKONSEPSI MENGGUNAKAN MODEL TSTS BERBANTUAN ALAT PERAGA TENTANG TEKANAN DI SMP ISLAM BAWARI - Rifa i, Muhammad; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of conducting this research is to know the effectiveness of the two stay two stray learning model (TSTS) as media in remediating the misconception of students of Bawari Islamic Junior High School in Pontianak on pressure material. The form of this research is one group pretest-posttest design. The sample of this research was VIII A. This class consisted of 32 students. The sample was designated by using purposive sampling technique. The data collection was diagnostic test through pre-test and post-test. The mean of percentage in the pre-test was 82.3% and the post-test was 15.6%. The mean of student misconception decrease was 81.1%. Based on the DQM test, the effectiveness of remediation was 81.1% (High level). The result of the Mc Nemar test was obtained 54.6 of is higher than 3.84 of . There was a significant result after remedial misconceptions by using TSTS on the pressure material.The teachers are expected to use TSTS as an alternative media to remediate student’s misconceptions on pressure material. Keywords: Remediation, misconception, two stay two stray model (TSTS), media, pressure.